RELIGIOSITY, BIOLOGICAL MARKERS AND HEALTH-RELATED QUALITY OF LIFE IN PATIENTS WITH HYPERTENSION - Santos, Daniela da Cunha dos; Abdala, Gina Andrade; Meira, Maria Dyrce Dias; Menslin, Douglas Jeferson; Pereira, Júlio Cesar Leal (International Journal of Research -GRANTHAALAYAH, 2022)
Motivation/Background: the adoption of a healthy lifestyle has a positive influence on the control of hypertension. Objective: The objective of this study was to analyze the effect of Spirituality and Health Workshops on biological markers and Health-Related Quality of Life of hypertensive patients. Method: This is a randomized controlled trial study in which an educational intervention was carried out and the religiosity and Quality of Life indices as well as the blood pressure and, Cortisol, C-Reactive Protein (CRP) and cholesterol were evaluated. Results: The intervention group experienced a lower diastolic pressure (p <0.05). There were no differences between intervention and control groups on systolic blood pressure, quality of life, somatic manifestations, mental state, CRP, and cholesterol levels. Conclusions: It was concluded that the intervention positively influenced the results, at least in one of the biological markers and the quality of life of this group.